2009
DOI: 10.1002/sca.20176
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and crystallographic study of remineralized surface on initial carious enamel treated with Galla chinensis

Abstract: To investigate the morphologic, chemical and crystallographic characters of remineralized surface on initial carious enamel treated with Galla chinensis, scanning electron microscopy equipped with energy dispersive analysis spectroscopy were used, and X-ray microdiffraction (microzone XRD) was used for the first time to analyze in situ the microzone crystallite of remineralized surface on carious enamel. Bovine sound enamel slabs were demineralized to produce initial carious lesion in vitro. Then, the lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Some studies showed that the chemical compounds of Galla chinensis could regulate the demineralization/remineralization balance by influencing the morphology, structure and chemical content of enamel crystals. 12,13 The special physicochemical property of polyphenols may assist during the modulation of biomineral crystal growth. Some studies indicated that natural polyphenol compounds, usually found in our food and drink, can efficiently modulate the growth of biominerals.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that the chemical compounds of Galla chinensis could regulate the demineralization/remineralization balance by influencing the morphology, structure and chemical content of enamel crystals. 12,13 The special physicochemical property of polyphenols may assist during the modulation of biomineral crystal growth. Some studies indicated that natural polyphenol compounds, usually found in our food and drink, can efficiently modulate the growth of biominerals.…”
Section: Introductionmentioning
confidence: 99%
“…The O was not modified in both carious and normal enamel layers ( Table 1). Although, the remineralization produced by hydroxyapatite consists in a deposition of a new apatite mineral into the eroded enamel surface scratches, carious surface [31] [37]. Acid attack is one of the major causes of enamel hydroxyapatite loss [25] [27].…”
Section: Resultsmentioning
confidence: 99%
“…These findings seem to support the formation of an 'enamel organic matrix-G. chinensis-calcium' complex that affects the mineral ion deposition. The mechanism is probably mediated by GCEs that enhance the remineralization of caries enamel (Zhang et al, 2009d).…”
Section: Remineralization-enhancing Propertymentioning
confidence: 99%